The essential John Nash - Nash, John F., Jr., 1928-2015; Kuhn, Harold W. (Harold William), 1925-2014; Nasar, Sylvia (2002)
"This book presents, for the first time, the full range of Nash's diverse contributions not only to game theory, for which he received the Nobel, but to pure mathematics, in which he commands even greater acclaim among academics. Included are nine of Nash's most influential papers, most them written over the decade beginning in 1949"--Jacket
1. Press release--The Royal Swedish Academy of Sciences -- 2. Autobiography. Photo essay -- 3. The game of hex -- 4. The bargaining problem -- 5. Equilibrium points in n-person games -- 6. Non-cooperative games (facsimile of Ph. D. thesis) --7. Non-cooperative games -- 8. Two-person cooperative games -- 9. Parallel control -- 10. Real algebraic manifolds -- 11. The imbedding problem for Riemannian manifolds -- 12. Continuity of solutions of parabolic and elliptic equations
Includes bibliographical references
Keywords: Game theory; Riemannian manifolds; Economics, Mathematical; Autobiographie; Biographie; Autobiographie; Biographie